Yolk utilization and growth during the early larval life of the Silver Perch, Bidyanus bidyanus (Mitchell, 1838) - Sulaeman; Fotedar, Ravi (2017)
The aim of this research was to investigate the yolk sac and oil globule utilization by silver perch (Bidyanus bidyanus) larvae produced from domesticated broodfish. The larvae were kept unfed in the holding tank, sampled, and investigated by image analysis software to determine various characteristics, such as the diameters of ova, water-hardened eggs, yolk-sac, oil globules, and the total length of larvae. The research illustrated that, with the exception of oil globule diameter, all other morphometric parameters were significantly lower (P < 0.05) when compared to the larvae from the wild broodfish. The yolk sac was completely absorbed at 96 h post-hatching (hph) and the oil globule was visible until 240 hph. The larvae exhibited predatory movements and tried to catch rotifer at 4 days post hatching (dph). However, the onset of feeding took place at 5 dph, while 100% of feeding occurred at 6 dph. During the first 96 h (h), larvae grew significantly faster than the next 144 h. Larvae encountered low mortalities (<10%) during the first 96 hph, before increasing significantly in the next 24 h and no unfed larvae survived post 240 h. The results also suggested that the exogenous feed should be available at 96 hph, which is well after the yolk sac is completely depleted. In addition, although most of eggs and larval performance from domesticated broodfish were inferior compared to the wild one, it has larger oil globule that could make longer of its mixed feeding period and therefore could have better in viability.